Evidence of heat sensitivity in people with Parkinson’s disease - Andrew P. Hunt; Aline Souza Pagnussat; Alexander Lehn; Daniel Moore; Daniel Schweitzer; E-Liisa Laakso; Ewald Hennig; Meg E. Morris; Graham Kerr; Ian Stewart (International Journal of Biometeorology, 2024)
Examining how heat affects people with Parkinson’s disease is essential for informing clinical decision-making, safety, well-being, and healthcare planning. While there is evidence that the neuropathology associated with Parkinson’s disease affects thermoregulatory mechanisms, little attention has been given to the association of heat sensitivity to worsening symptoms and restricted daily activities in people with this progressive disease. Using a cross-sectional study design, we examined the experiences of people diagnosed with Parkinson’s disease in the heat. Two-hundred and forty-seven people completed an online survey (age: 66.0 ± 9.2 years; sex: male = 102 (41.3%), female = 145 (58.7%)), of which 195 (78.9%) reported becoming more sensitive to heat with Parkinson’s disease. Motor and nonmotor symptoms worsened with heat in 182 (73.7%) and 203 (82.2%) respondents, respectively. The most commonly reported symptoms to worsen included walking difficulties, balance impairment, stiffness, tremor, fatigue, sleep disturbances, excess sweating, difficulty concentrating, and light-headedness when standing. Concerningly, over half indicated an inability to work effectively in the heat, and nearly half reported that heat impacted their ability to perform household tasks and social activities. Overall, heat sensitivity was common in people with Parkinson’s disease and had a significant impact on symptomology, day-to-day activities and quality of life.

The hidden hand is perceived closer to midline - Hassan G. Qureshi; Annie A. Butler; Graham K. Kerr; Simon C. Gandevia; Martin E. Héroux (Experimental Brain Research, 2019)

Dexamphetamine effects on prepulse inhibition (PPI) and startle in healthy volunteers - Kate Chitty; Matthew A. Albrecht; Kyran Graham; Chantelle Kerr; Joseph W. Y. Lee; Rajan Iyyalol; Mathew T. Martin-Iverson (Psychopharmacology, 2014)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

The effect of extended wake on postural control in young adults - Simon S. Smith; Tiffany Cheng; Graham K. Kerr (Experimental Brain Research, 2012)

Contributions of vision–proprioception interactions to the estimation of time-varying hand and target locations - Hideyuki Tanaka; Charles Worringham; Graham Kerr (Experimental Brain Research, 2009)